ANTIHYPERGLYCEMIC ACTIVITY OF A FLOUR MIX PREPARATION FROM Amorphophalus campanulatus (ELEPHANT FOOT YAM) AGAINST STREPTOZOTOCIN – NICOTINAMIDE INDUCED DIABETIC WISTAR RATS (Applied Biological Research, 2025)
Elephant foot yam (Amorphophallus campanulatus) is a tropical tuber with significant nutritional and medicinal potential but is underutilized due to its anti-nutritional factors. This study evaluated the anti-hyperglycaemic effects of resistant starch (RS) derived from A. campanulatus in streptozotocin–nicotinamide (STZ-NIC) induced diabetic Wistar rats. RS was prepared by autoclaving, retrogradation, and enzymatic hydrolysis. Acute toxicity tests confirmed safety up to 2000 mg kg⁻¹. Diabetic rats treated with RS at 100 and 200 mg kg⁻¹ for 28 days exhibited a significant reduction in fasting blood glucose levels. In the diabetic control group, blood glucose was 284.8 ± 6.1 mg dL⁻¹ on day 1 and 293.2 ± 6.5 mg dL⁻¹ on day 28. RS treatment also resulted in improved HbA1c, urea, and creatinine levels, alongside increased plasma insulin, liver glycogen, total protein, and body weight, comparable to the standard drug glibenclamide. Histopathological analysis revealed β-cell preservation in RS-treated groups. Additionally, RS promoted the growth of beneficial gut microbiota, reinforcing its prebiotic role. These findings indicate that RS from A. campanulatus holds promise as a functional food ingredient with anti-diabetic and gut-modulatory benefits.
Keywords: Elephant foot yam; functional food; gut microbiota; glycemic control; plasma insulin; type-2 diabetes